2016
DOI: 10.1093/aobpla/plw078
|View full text |Cite
|
Sign up to set email alerts
|

The global distribution of bamboos: assessing correlates of introduction and invasion

Abstract: Bamboos are one of the most economically important plant groups globally, but this world-wide trade creates risks of invasions. Here we identified 1662 species of bamboo, of which almost a seventh (232) have been introduced outside their native range, with Asiatic and larger species preferred. Only 12 species were found to have become invasive. However, invasiveness was found to be more a function of human-usage than specific species traits, suggesting the recent upsurge in bamboo cultivation could pose future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
96
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 95 publications
(146 reference statements)
1
96
0
4
Order By: Relevance
“…The search represents all taxa that are likely to have recorded impacts in the literature (see Figure ). The remaining bamboos that were not evaluated in this study are therefore classed as NE—Not Evaluated under the EICAT scheme (although some of these can be considered as NA—No Alien Population according to Canavan et al, ). Of the 135 taxa that were included in the study, we found 65 references which contained details on 20 species for which recorded environmental impacts could be scored using the EICAT scheme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search represents all taxa that are likely to have recorded impacts in the literature (see Figure ). The remaining bamboos that were not evaluated in this study are therefore classed as NE—Not Evaluated under the EICAT scheme (although some of these can be considered as NA—No Alien Population according to Canavan et al, ). Of the 135 taxa that were included in the study, we found 65 references which contained details on 20 species for which recorded environmental impacts could be scored using the EICAT scheme.…”
Section: Resultsmentioning
confidence: 99%
“…The geographic distribution and localities of reported impacts of native and non‐native bamboos. Top: the native and non‐native distribution of bamboo species (data retrieved from Canavan et al, ). Bottom: localities where impacts have been reported in the native and non‐native ranges of bamboos based on a systematic global literature search using a modified version of the International Union for Conservation of Nature’s (IUCN's) Environmental Impact Classification of Alien Taxa (EICAT) scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Many plants (c. 70% in the temperate zone) possess the capacity to reproduce vegetatively via rhizomes and stolons (Klimeš, Klimešova, Hendriks, & van Groenendael, 1997). Such clonal plants, including many invasive exotics (Canavan et al, 2016;Liu et al, 2006;Pyšek, 1997), often dominate terrestrial habitats, such as grasslands, salt marshes, and understoreys of temperate and boreal forests. Clonal plants also appear to increase its abundance in response to global change drivers such as habitat fragmentation (Tomimatsu et al, 2011) and nutrient deposition (Dickson, Mittelbach, Reynolds, & Gross, 2014;Gough et al, 2012), with important consequences for community structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…“Bamboo” is the common term for plants in the subfamily Bambusoideae, a diverse group with c. 121 genera and 1,662 species worldwide (Canavan et al, ). These grasses are distributed mainly in tropical and subtropical areas, but also occur in mild‐temperate regions in south and southeast Asia (Lobovikov, Ball, Guardia, & Russo, ).…”
Section: Introductionmentioning
confidence: 99%